The Impact of Corruption on Environmental Quality in the Developing Countries of ASEAN–3: The Application of the Bound Test - Ridzuan, Abdul Rahim; Sapuan, Noraina Mazuin; Abd Rahman, Nur Hayati; Borhan, Halimahton; Othman, Azhana (International Journal of Energy Economics and Policy, 2019)
This paper has examined the short-run and long-run relationships between economic growth, energy consumption, foreign direct investment, trade openness, financial development, corruption, urban population and carbon dioxide (CO2) emissions in three developing countries of ASEAN, i.e. Malaysia, Indonesia and the Philippines (ASEAN–3), with data from 1970 to 2017. Special emphasis has been given to the level of corruption in these three countries as several recent media releases have reported that many firms have been conducting unlawful activities by importing large amounts of waste from developed countries and these wastes, including plastic waste, have been burnt in open spaces and have caused higher releases of carbon emissions. Long-run elasticity results have proven that the higher level of corruption in these three ASEAN countries has caused more environmental pollution. Meanwhile, other tested variables have shown mixed findings across the three tested countries. Improvement of institutional quality is urgently needed for ASEAN-3 countries by adopting more transparent laws and the imposition of heavier penalties on corrupt officials and even on the entrepreneurs who have engaged in unlawful business activities that have caused higher environmental pollution. Keywords: Environmental Quality, Corruption, Bound Estimation, ASEAN-3. JEL Classifications: F64, O57, P28 DOI: https://doi.org/10.32479/ijeep.8135